1974
DOI: 10.1364/ao.13.000396
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Clad Optical Waveguides: Analytical and Experimental Study

Abstract: Planar optical waveguides consisting of thin dielectric films with metal cladding have been investigated theoretically and experimentally. A computer program was devised to provide the phase and attenuation constants and wavefunctions for TE and TM modes in symmetric and asymmetric guides. Approximate expressions suitable for slide-rule calculation were also derived. Numerical results and illustrations are given for films of photoresist with Al, Ag, and Au cladding. Direct measurements of the attenuation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(89 citation statements)
references
References 12 publications
2
83
0
4
Order By: Relevance
“…The mirrors may be either dielectric stacks or, in some cases, metals. 6,7 It has been clearly demonstrated that the boundary conditions imposed by such planar microcavity systems can modify the spatial and spectral distribution of the emitted radiation from such devices 4 and also the spontaneous emission lifetime of the emitter. 8,9 However, the extent to which spontaneous emission may be controlled is limited by the planar symmetry of the microcavity.…”
Section: Introductionmentioning
confidence: 99%
“…The mirrors may be either dielectric stacks or, in some cases, metals. 6,7 It has been clearly demonstrated that the boundary conditions imposed by such planar microcavity systems can modify the spatial and spectral distribution of the emitted radiation from such devices 4 and also the spontaneous emission lifetime of the emitter. 8,9 However, the extent to which spontaneous emission may be controlled is limited by the planar symmetry of the microcavity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar waveguides with metal-insulator-metal have been intensively studied both theoretically [26][27][28][29] and experimentally. 30,31 By inserting InP/InGaAs/ InP heterostructure in the middle, our configuration enables compensation for the metal loss by optical gain in the InGaAs layer. The entire structure can be pumped using electrical injection to achieve optical amplification or lasing.…”
Section: Nanolasers Based On Misim Waveguidesmentioning
confidence: 99%
“…50 nm), with widths of 150À200 nm, are repeated with periods of 200 to 300 nm, forming an inter-MIM spacing of 10À80 nm. MIM structures can be viewed as nanoscale planar waveguides, 15 and individual MIM elements have modes confined inside the dielectric region (referred to as waveguide mode). Localized resonances result from the FabryÀPerot (FP)-type resonator formed within the MIM waveguide, terminated at both ends.…”
mentioning
confidence: 99%
“…Localized resonances result from the FabryÀPerot (FP)-type resonator formed within the MIM waveguide, terminated at both ends. The propagation wavevector β SPP and effective index n eff = β SPP /k 0 of the fundamental TM mode of a MIM waveguide can be calculated by solving for β SPP in the following equation 15 …”
mentioning
confidence: 99%